Horizontal shear force for different arrangements of coupling bars in precast concrete slab with and without steel fibre - Awaludin, Safiah Zaleha (2018)
In precast concrete slab, the coupling bars and in-situ concrete act as the precast slab panel connection. The design of coupling bars based on Eurocode 2 must be able to resist the horizontal shear force and the U-loop bar must also be design to carry this force. The placing of coupling bars as the connection to the precast concrete floor is to ensure the continuity of precast floor diaphragm. In this study, in-situ steel fibre grouting was used to fill the connection between the precast concrete slab instead of the conventional method using in-situ concrete and at the same time, the number of coupling bars was also reduced. This study was conducted to determine the horizontal shear force for different arrangement of coupling bars with and without steel fibre. The experimental test using push-off test method was conducted. The results of push-off test for specimens with different arrangement of coupling bars were compared with the control specimen. The steel fibre grouting shows the improvement in term of ultimate strength and ductility of the in-situ grout. Besides, the additional of steel fibre in grout also influence the ultimate horizontal load of the specimen compare with the plain grout. The push-off test shows that the specimen that have only two numbers of coupling bars and with in-situ steel fibre grouting performed better than the control specimen.